A novel pseudovirus‐based mouse model of SARS-CoV-2 infection to test COVID-19 interventions - Ssu-Hsueh Tseng; Brandon Lam; Yu Jui Kung; John Lin; Li Liu; Ya Chea Tsai; Louise Ferrall; Richard B. S. Roden; T. C. Wu; Chien-Fu Hung (Journal of Biomedical Science, 2021)
Abstract Background The spread of SARS-CoV-2, the virus that causes Coronavirus Disease 2019 (COVID-19), has been characterized as a worldwide pandemic. Currently, there are few preclinical animal models that suitably represent infection, as the main point of entry to human cells is via human angiotensin-converting enzyme 2 (ACE2) which is not present in typical preclinical mouse strains. Additionally, SARS-CoV-2 is highly virulent and unsafe for use in many research facilities. Here we describe the development of a preclinical animal model using intranasal administration of ACE2 followed by non-infectious SARS-CoV-2 pseudovirus (PsV) challenge. Methods To specifically generate our SARS-CoV-2 PsV, we used a lentivirus system. Following co-transfection with a packaging plasmid containing HIV Gag and Pol, luciferase-expressing lentiviruses, and a plasmid carrying the SARS-CoV-2 spike protein, SARS-CoV-2 PsVs can be isolated and purified. To better understand and maximize the infectivity of SARS-CoV-2 PsV, we generated PsV carrying spike protein variants known to have varying human ACE2 binding properties, including 19 deletion (19del) and 19del + D614G. Results Our system demonstrated the ability of PsVs to infect the respiratory passage of mice following intranasal hACE2 transduction. Additionally, we demonstrate in vitro and in vivo manipulability of our system using recombinant receptor-binding domain protein to prevent PsV infection. Conclusions Our PsV system is able to model SARS-CoV-2 infections in a preclinical mouse model and can be used to test interventions or preventative treatments. We believe that this method can be extended to work in various mouse strains or to model infection with different coronaviruses. A simple in vivo system such as our model is crucial for rapidly and effectively responding to the current COVID-19 pandemic in addition to preparing for future potential coronavirus outbreaks.